Teaching Mindfulness A Practical Guide for Clinicians and Educators - McCown, Donald; Reibel, Diane; Micozzi, Marc S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The applications and use of mindfulness-based interventions in medicine, mental health care, and education have been expanding as rapidly as the empirical evidence base that is validating and recommending them. This growth has created a powerful demand for professionals who can effectively deliver these interventions, and for the training of new professionals who can enter the fold. Ironically, while the scientific literature on mindfulness has surged, little attention has been paid to the critical who and how of mindfulness pedagogy. Teaching Mindfulness is the first in-depth treatment of the person and skills of the mindfulness teacher. It is intended as a practical guide to the landscape of teaching, to help those with a new or growing interest in mindfulness-based interventions to develop both the personal authenticity and the practical know-how that can make teaching mindfulness a highly rewarding and effective way of working with others. The detail of theory and praxis it contains can also help seasoned mindfulness practitioners and teachers to articulate and understand more clearly their own pedagogical approaches. Engagingly written and enriched with vignettes from actual classes and individual sessions, this unique volume: Places the current mindfulness-based interventions in their cultural and historical context to help clarify language use, and the integration of Eastern and Western spiritual and secular traditions Offers a highly relational understanding of mindfulness practice that supports moment-by-moment work with groups and individuals Provides guidance and materials for a highly experiential exploration of the reader's personal practice, embodiment, and application of mindfulness Describes in detail the four essential skill sets of the mindfulness teacher Proposes a comprehensive, systematic model of the intentions of teaching mindfulness as they are revealed in the mindfulness-based interventions Includes sample scripts for a wide range of mindfulness practices, and an extensive resource section for continued personal and career development Essential for today's practitioners and teachers of mindfulness-based interventions Teaching Mindfulness: A Practical Guide for Clinicians and Educators brings this increasingly important discipline into clearer focus, opening dialogue for physicians, clinical and health psychologists, clinical social workers, marriage and family therapists, professional counselors, nurses, occupational therapists, physical therapists, pastoral counselors, spiritual directors, life coaches, organizational development professionals, and teachers and professionals in higher education, in short, everyone with an interest in helping others find their way into the benefits of the present moment.
Clinical and Cultural Context -- Getting Grounded (In Our Own Instability) -- A History Exercise to Locate (3z(BMindfulness(3y (BNow -- Defining Mindfulness for the Moment -- Authenticity, Authority, and Friendship -- The Person of the Teacher -- The Skills of the Teacher -- Towards an (3z(BEmpty(3y (BCurriculum -- Organizing the Intentions of Teaching -- Fulfilling the Intentions of Teaching -- Practice Scripts and Descriptions -- Erratum to: Practice Scripts and Descriptions.s
Keywords: Medicine; Alternative medicine; Family medicine; Emergency medicine; Rehabilitation; Psychology, clinical; Medicine & Public Health; Complementary & Alternative Medicine; Primary Care Medicine; Health Psychology; Clinical Psychology; Rehabilitation; General Practice / Family Medicine